KONSEP ORGANIZATIONAL INTELLIGENCE DALAM KEPEMIMPINAN PENDIDIKAN - Windaryati; Sundani; Suryawati; Ahmad Hariyadi; Slamet Utomo (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2023)
This study aims to see and provide different views regarding organizational intelligence on educational leadership, namely the ability to direct organizations to move according to the development direction they want. Regarding how important the organizational intelligence of a leader is in contributing to the organization that their leads. This research uses the literature review method or literature study, with stages (1) objective; 2) inclusion criteria; 3) search strategy; (4) data collection; (5) quality of study; and (6) result synthesis data. This technique is carried out with the aim of disclosing various theories that are relevant to the problems being faced or researched as reference material in the discussion of research results. The results of this study showed that organizational intelligence is able to make a leader encourage his organization to move towards the target that has been set, namely people who have successfully built a clear self-image, because before followers are moved, they would want to recognize who their leader was, does the leader deserve to be a role model?.